High-sensitivity and low-loss SAW accelerometer base on phononic crystals - Yuan Rui; Xu Zhangliang; Wei Song (Acta Acustica)
The cantilever beam-based surface acoustic wave (SAW) accelerometer has a fast response time and high sensitivity, making it widely used in vibration detection of mechanical structures. In the fabrication and production of the sensor, the sensitivity and loss of the device have always been the key factors of concern. Here, a kind of SAW acceleration resonator based on nanopillar phononic crystals (PnCs) are proposed, and its properties of resonance frequency, phase velocity, quality (Q) factor, electromechanical coupling coefficient, resonance bandgap and acceleration sensitivity are numerically simulated by the finite element method (FEM). The influence of piezoelectric thin film (AlN) thickness and aluminum (Al) interdigital transducers (IDTs) thickness on the performance of the SAW resonator is analyzed with single pair IDT model simulations. It can be seen that PnCs can make SAW in the bandgap (766 MHz–864 MHz) spread along a fixed path or confined array area, effectively reducing acoustic energy loss. The presence of PnCs can improve the resonance frequency, phase velocity, Q factor and acceleration sensitivity of SAW resonator. Especially, the PnCs-SAW accelerometer exhibits a higher Q factor of 1135.3 and linear sensitivity of −4.9 kHz/g within the detection range of 0–70 g. This work is expected to provide a theoretical guidance for the development of SAW acceleration sensors with lower losses and higher sensitivity, offering new ideas for the diverse design of SAW devices.